Access to Career Education and Work-related Learning: a complex literature review on equity and inclusion - Daniela Frison (Firenze University Press, 2022)
The study presents a systematic literature review based on relevant articles at a national and international level and focused on equity and inclusion in the access to Career Education (CE) and Work-Related Learning (WRL) Opportunities. The systematic review was carried out following a defined process and the research identified 22 papers, 7 conceptual and 17 empirical. The study aims to identify factors that can facilitate or hinder access to CE and WRL and strategies by schools and universities to improve it.   Accesso a Career Education e Work-Related Learning: una analisi complessa della letteratura su equità e inclusione. Il contributo presenta un'analisi sistematica della letteratura rintracciata a livello nazionale e internazionale con l'obiettivo di indagare i temi di equità e inclusione nell'accesso a programmi, progetti, interventi di Career Education (CE) e Work-Related Learning (WRL). I criteri di selezione adottati hanno condotto all'identificazione di 22 contributi, 7 concettuali e 15 empirici. Lo studio intende identificare fattori che possono facilitare o ostacolare l'accesso a CE e WRL e strategie che scuole e università possono attivare per incoraggiarlo.